2019
DOI: 10.1371/journal.pone.0220855
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the factors impacting on access and acceptance of sexual and reproductive health services provided by adolescent-friendly health services in Nepal

Abstract: Adolescent-friendly health programs have been in place in Nepal since 2008, yet uptake of the services for sexual and reproductive health remains suboptimal. For uptake of these services to improve, a rich understanding is needed of the factors impacting their acceptance and utilization from the perspectives of adolescents, health care staff, and key community informants. This study applied a qualitative research design involving six focus groups with 52 adolescents and in-depth interviews with 16 adolescents,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
71
3
7

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 61 publications
15
71
3
7
Order By: Relevance
“…Some service providers suggested that it would be inappropriate for primary school adolescents to access SRH services irrespective of being between 10-19 years because they are not considered to be mature enough to make their own decisions regarding sexual health. These ndings are similar to what was found by other studies that adolescents less than 12 or 14 years old cannot access SRH services without the consent of their parents, or services were rejected to be provided by healthcare providers, especially when it comes to HIV related services [24,26].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Some service providers suggested that it would be inappropriate for primary school adolescents to access SRH services irrespective of being between 10-19 years because they are not considered to be mature enough to make their own decisions regarding sexual health. These ndings are similar to what was found by other studies that adolescents less than 12 or 14 years old cannot access SRH services without the consent of their parents, or services were rejected to be provided by healthcare providers, especially when it comes to HIV related services [24,26].…”
Section: Discussionsupporting
confidence: 90%
“…These barriers play a role in affecting the general quality of services. The ndings are consistent with those from other low-and middle-income countries (LMICs) regarding the numerous barriers adolescents face while accessing SRH services [24,25]. This calls for policymakers, activists, and the community to formulate methodologies to ensure that the SRH services accessibility, availability, as well as the quality of services provided are considered while designing health services provision to ensure that the "no one left behind" principle is applied to achieve Sustainable Development Goal 3 [28].…”
Section: Discussionsupporting
confidence: 86%
“…Awkwardly, majority of providers in the study were mentioning the above challenges as limiting factors for utilization of the service. The ndings of this study were also congruent with studies done in Ethiopia [24], Ghana [25] and Nepal [26]. In addition, according to our ndings, adolescents wanted to be served by providers of older age and same sex.…”
Section: Discussionsupporting
confidence: 90%
“…Because, I see that adolescents are in uenced by peers not by theirs own decision." [Female, Age:[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] Health Extension] Another participant witnessed disclosing secrecy of adolescents from his experience. "Healthcare providers have a problem of keeping secrets about adolescent and sexual issues.…”
mentioning
confidence: 99%
“…The observed variation across the countries may be attributable to variation in societal acceptance of childbearing at teenage (15-19 years). Teens are likely to access the service of skilled personnel if they feel appreciated and welcomed by healthcare providers and the society in which they live [25]. Women who are advanced in age might be discouraged by the attitude of healthcare providers if they had a negative experience in the past, unlike those in the 15-19 age category who might be having first deliveries and, hence, fewer chances of negative delivery experience [26].…”
Section: Discussionmentioning
confidence: 99%